Formulation and Quality Evaluation of Breakfast Cereals from Acha, Bambara Groundnut and Carrot Composite Flours - Okoye, J. I.; Igwego, N. G.; Ajawobu, I, O.; Onwuchuruba–Nwadike, S. C. (Archives of Current Research International, 2025)
The aim of this present study was to evaluate the proximate composition, microbiological, functional and pasting properties of breakfast cereals produced from acha, Bambara groundnut and carrot flour blends. Breakfast is regarded as the most important meal of the day because food consumed at breakfast seems to be more utilized than the same amount eaten at night. Breakfast cereals are commonly known as foods which have been fully or partially prepared that may need to be reconstituted, preheated in a vessel or allowed to thaw if frozen before consumption or eaten directly without further treatment. Acha grains, Bambara groundnut seeds and carrot fruits which were sourced locally were separately processed into flours. The Bambara groundnut and carrot flours were used at varying replacement levels (5-30%) with malted acha flour to produce breakfast cereals with the breakfast cereal produced from 100% malted acha flour as control. The proximate composition, microbiological, functional and pasting properties of the breakfast cereal products were determined using standard methods. The proximate composition of the samples revealed that the moisture, crude protein, fat, ash and crude fibre contents of the products increased significantly (p<0.05) with increased substitution of Bambara groundnut and carrot flours, while the carbohydrate and energy contents decreased. The microbial counts of the breakfast cereals showed that the total viable count ranged from 0.50 x 104 to 1.60 x 104cfu/g, while the coliform and fungal counts were nil. The functional properties also showed that the bulk density, solubility index, water absorption, oil absorption and foam capacities of the samples increased significantly (p<0.05) with increase in the addition of Bambara groundnut and carrot flours, while the gelation and swelling capacities decreased. The pasting properties (peak, trough, breakdown, setback and final viscosities), as well as the peak time and pasting temperature of the samples, also increased significantly (p<0.05) with increased substitution of Bambara groundnut and carrot flours from 37.15 to 92.83 RVU, 58.15 to 116.70 RVU, 48.89 to 91.05 RVU, 38.27 to 88.28 RVU, 63.03 to 93.53 RVU, 7.73 to 8.85 min and 31.17 to 98.370C, respectively. The study, therefore, revealed that the addition of Bambara groundnut and carrot flours to acha flour at the levels of 20 to 30 % in the preparation of breakfast cereals increased the crude protein, fat, ash and crude fibre contents as well as the pasting and some functional properties of the composite flour breakfast cereals compared to the control.